Metaproteogenomic Profiling of Chemosynthetic Microbial Biofilms Reveals Metabolic Flexibility During Colonization of a Shallow-Water Gas Vent - Patwardhan, Sushmita; Smedile, Francesco; Giovannelli, Donato; Vetriani, Costantino (Frontiers in Microbiology, 2021)
Tor Caldara is a shallow-water gas vent located in the Mediterranean Sea, with active venting of CO2, H2S. At Tor Caldara, filamentous microbial biofilms, mainly composed of Epsilon- and Gammaproteobacteria, grow on substrates exposed to the gas venting. In this study, we took a metaproteogenomic approach to identify the metabolic potential and in situ expression of central metabolic pathways at two stages of biofilm maturation. Our findings indicate that inorganic reduced sulfur species are the main electron donors and CO2 the main carbon source for the filamentous biofilms, which conserve energy by oxygen and nitrate respiration, fix dinitrogen gas and detoxify heavy metals. Three metagenome-assembled genomes (MAGs), representative of key members in the biofilm community, were also recovered. Metaproteomic data show that metabolically active chemoautotrophic sulfide-oxidizing members of the Epsilonproteobacteria dominated the young microbial biofilms, while Gammaproteobacteria become prevalent in the established community. The co-expression of different pathways for sulfide oxidation by these two classes of bacteria suggests exposure to different sulfide concentrations within the biofilms, as well as fine-tuned adaptations of the enzymatic complexes. Taken together, our findings demonstrate a shift in the taxonomic composition and associated metabolic activity of these biofilms in the course of the colonization process.